Occupational change and mobility among employed and unemployed job seekers - Simonetta Longhi; Mark Taylor (University of Essex, Institute for Social and Economic Research (ISER), 2011)
We use data from the Labour Force Survey to show that employed and unemployed job seekers in Great Britain originate from different occupations and find jobs in different occupations. We find substantial differences in occupational mobility between job seekers: employed job seekers are most likely to move to occupations paying higher average wages relative to their previous occupation, while unemployed job seekers are most likely to move to lower paying occupations. Employed and unemployed job seekers exhibit different patterns of occupational mobility and, therefore, do not accept the same types of jobs.
Keywords: J01; J20; J29; J62; J64; 330; on-the-job search; unemployment; occupations; Arbeitsmarkt; Arbeitslosigkeit; Arbeitsuche; Arbeitsmobilität; Lohnniveau; Großbritannien